1999
DOI: 10.1111/j.1365-2141.1999.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IgG monoclonal anti‐cardiolipin/anti‐β2GP1 antibodies from two patients with antiphospholipid syndrome reveals three species of antibodies

Abstract: Antiphospholipid antibodies (aPL), including antibodies detected in anti-cardiolipin (aCL) enzyme-linked immunosorbent assays and in lupus anticoagulant (LA) tests, are strongly associated with recurrent thrombosis and recurrent fetal loss, i.e. the antiphospholipid syndrome (APS). Although recent studies suggest that most APS-associated aCL are directed against the phospholipid (PL)-binding plasma protein beta2-glycoprotein 1 (beta2GP1), the precise nature of aCL binding specificities remains controversial. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 44 publications
3
74
0
1
Order By: Relevance
“…Zhu et al (40) reported 2 human IgG monoclonal antibodies, IS1 and IS2, that bound bovine but not human ␤ 2 GPI. Sequence analysis later showed that these antibodies were derived from the same B cell clone (41).…”
Section: Lambrianides Et Almentioning
confidence: 99%
“…Zhu et al (40) reported 2 human IgG monoclonal antibodies, IS1 and IS2, that bound bovine but not human ␤ 2 GPI. Sequence analysis later showed that these antibodies were derived from the same B cell clone (41).…”
Section: Lambrianides Et Almentioning
confidence: 99%
“…Anti-cardiolipin mAbs IS4 and IS6 were derived from an APS patient and hybridomas and were generated as described (29). The CD4 inducible anti-HIV-1 gp120 mAb 17b (30,31) was provided by Dr. J. Robinson (Tulane University, New Orleans, LA).…”
Section: Antibodiesmentioning
confidence: 99%
“…IgG fractions from APS patients (APS-IgG) and control sera of SLE patients without APS (SLE-IgG) and healthy subjects (normal controls (NC-IgG) were purified on protein G columns (HiTrap Protein G; Pharmacia Biotech, Uppsala, Sweden). Two mAbs against cardiolipin (CL) (CL15 and IS4) were derived from EBV-transformed cell lines from two APS patients, whose clinical and serologic characteristics have previously been described (43). CL15 and IS4 were generated as the conventional aCL (by being screened against CL in the presence of bovine serum).…”
Section: Patients Blood Samples and Isolation Of Iggmentioning
confidence: 99%